Efektivitas Model Pembelajaran Keterampilan Bulutangkis Berbasis Multimedia terhadap Peningkatan Hasil Belajar Mahasiswa di Perguruan Tinggi - Kurniawan, Edi (Universitas Hamzanwadi, 2024)
This study aims to determine the impact of the effectiveness of multimedia-based learning models on student badminton skills learning outcomes comprehensively. This study used a quasi experimental design method with a pretest posttest control group design approach. The study population was sports education students from three universities in West Java, with a sample of 150 students divided into 75 students per group. This instrument uses an observation sheet-based assessment, with each indicator assessed. The results showed a significant improvement in the experimental group, with the posttest score (mean = 82.6) being significantly higher compared to the control group (mean = 68.4). An independent t-test further confirmed the significant difference between the two groups (t = 8.721, p < 0.05), demonstrating the superiority of the multimedia-based approach. The model effectively improved students' understanding, skill mastery and motivation through an interactive and engaging learning environment. The multimedia-based learning model is significantly effective in improving students' badminton skills learning outcomes compared to the conventional method.